2022
DOI: 10.3390/econometrics10020026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic News on the Cryptocurrency Market and Gold Returns: A Quantile-on-Quantile Regression Analysis

Abstract: In this paper, we investigate the relationship between the RavenPack news-based index associated with coronavirus outbreak (Panic, Sentiment, Infodemic, and Media Coverage) and returns of two commodities—Bitcoin and gold. We utilized the novel quantile-on-quantile approach to uncover the dependence between the news-based index associated with coronavirus outbreak and Bitcoin and gold returns. Our results reveal that the daily levels of positive and negative shocks in indices induced by pandemic news asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Bitcoin’s underlying technology, blockchain, also has several benefits, including distributed ledger, decentralization, information transparency, tamper-proof design, and openness (Xu et al 2019 ). In line with Chen et al ( 2022 ), Mahdi and Al–Abdulla ( 2022 ), and Banerjee et al ( 2022 ), we obtained coronavirus indices from RavenPack. RavenPack Coronavirus Media Monitor synthesizes the feelings (mood) expressed in news reports and public posts, which are then converted into convenient metrics (Rahadian and Nurfitriani 2022 ).…”
Section: Quantitative Frameworksupporting
confidence: 87%
See 2 more Smart Citations
“…Bitcoin’s underlying technology, blockchain, also has several benefits, including distributed ledger, decentralization, information transparency, tamper-proof design, and openness (Xu et al 2019 ). In line with Chen et al ( 2022 ), Mahdi and Al–Abdulla ( 2022 ), and Banerjee et al ( 2022 ), we obtained coronavirus indices from RavenPack. RavenPack Coronavirus Media Monitor synthesizes the feelings (mood) expressed in news reports and public posts, which are then converted into convenient metrics (Rahadian and Nurfitriani 2022 ).…”
Section: Quantitative Frameworksupporting
confidence: 87%
“…Furthermore, the positive impact of the pandemic sentiment on Bitcoin returns is consistent with Goodell and Goutte ( 2021 ). Additionally, Mahdi and Al–Abdulla ( 2022 ) showed that Bitcoin returns increase as the frequency of fear-related headlines increases. Following Shrotryia and Kalra ( 2021 ) and Marobhe ( 2022 ), the empirical findings reject any uneven behavioral shape throughout the pandemic disorder.…”
Section: Econometric Findingsmentioning
confidence: 99%
See 1 more Smart Citation